Negotiating Tradition, Modernity, and Intergenerational Roles: Chinese Multigenerational Family RV Tourism in Western Contexts - Dong, Ye (Auckland University of Technology, 2026)
This thesis investigates the underexplored phenomenon of Chinese multigenerational family tourism through recreational vehicle (RV) travel in Western contexts. Despite the rapid expansion of Chinese family tourism research, limited scholarly attention has been given to three-generation family journeys or RV travel, resulting in gaps in the literature. Conceptualising RV tourism as a mobile cultural dimension, the research examines how tradition and modernity, collectivism and individuality, and intergenerational roles are negotiated across the pre-trip, on-trip, and post-trip phases. To capture the complexity of multigenerational dynamics in RV family tourism, this research employed Charmaz's Constructivist Grounded Theory methodology, complemented by netnography and adapted whole-family interviews, and adopted a child-inclusive, parent-comprehensive, and grandparent-sensitive design. Data were collected between 2022 and 2024 from eight families across three generations, using methods adapted to Chinese cultural norms and pandemic conditions. The analysis combined iterative grounded theory coding of interviews with thematic mapping of digital platform content. This integration of semi-structured interviews with netnography captured narrated experiences and digital representations, allowing for comprehensive insights into the co-construction of family voices and identities. This approach advances methodological innovation in studying Chinese multigenerational tourism in mobile, digitally mediated, cross-cultural contexts. Findings demonstrate that RV tourism serves as a site of cultural transmission, emotional restoration, digital detox, aspirational consumption, and the tension inherent in the nexus of education, work, and leisure travel. The three findings chapters examine grandparents, parents, and children separately. Chapter 7 presents thematic and theoretical models grounded in empirical data to capture the distinctive dynamics of each generational cohort. Chapter 8 advances this synthesis by situating the integrated framework within a broader theoretical model. This scaffolded structure ensures both depth in understanding generational particularities and breadth in theorising their interconnections. The research contributes original, integrative, and theoretical models, including the Family Dynamics in RV Travel Model and the Xiaozi Dimensions in RV Family Tourism. The thesis makes significant theoretical contributions by extending Bourdieu's framework through the introduction of environmental and learning capital. It reconceptualises harmony as negotiated resilience; and by developing the culturally grounded Chinese 4X Framework (filial duty: Xiao孝; efficiency: Xiao 效; positivity: Xiao 笑; and lifestyle aspiration: Xiaozi 小资), it captures the interplay between heritage and aspiration. Contributions to cultural value are made by situating the interdependent Chinese self within mobile and digitalised contexts, illustrating how intergenerational bonds are recalibrated through emotional labour, spatial intimacy, and social media representation, while reinterpreting Chinese values such as Shan Shui (mountain–water aesthetics), Zhong Yong (the Doctrine of the Mean), and harmony within diversity. These dimensions are situated within contemporary leisure travel practices and developed into a culturally-nuanced framework, the Theoretical Framework of Cross-Cultural Dynamics of Chinese Family RV Travel in Western Countries. The diversity of multigenerational expressions underscores society's capacity to experiment, adapt, and manage changing circumstances. By documenting and analysing the practice of multigenerational Chinese family RV tourism in a Western context, this thesis enriches tourism scholarship. It advances Chinese culture-centred perspectives within the broader global academic discourse.